P077 Dysregulated miR-125a promotes joint angiogenesis through enhanced glycolysis. (March 2019) - Wade, SM; Ohnesorge, N; McLaouglin, H; Biniecka, M; McGarry, T; Canavan, M; Veale, DJ; Kennedy, B; Fearon, U
Abstract : Career situation of first and presenting author: Post-doctoral fellow. Introduction: Psoriatic arthritis (PsA) is characterised by an early vascular phase essential for pannus growth, immune responses and disease progression. Recently, numerous studies have highlighted the emerging importance of endothelial cell (EC) metabolism in disease. Herein, we propose microRNA, miR-125, modulates EC bioenergetics and orchestrates joint angiogenesis as characterised by ex-vivo associations, in-vitro assays and novel CRISPR/cas9 in-vivo zebrafish models. Objectives: To elucidate the role of miR-125a and endothelial cell metabolism in dysfunctional angiogenesis in PsA. Methods: MiRNA levels were quantified in synovial tissue and compared to macroscopic synovial vascularity. HUVECs were transfected with anti-miR-125a for 24 hour and tube formation assays, transwell invasion, wound repair and gene expression analysis performed. Real-time analysis of anti-miR-125 treated ECs metabolism was assessed using the XF-24 Extracellular Flux Analyzer (Seahorse Bioscience). Metabolism markers (GAPDH/PKM2/GLUT1/ATP) were assessed ex vivo by immunohistochemistry. In vivo, miR-125a CRISPR/Cas9-based knock-out zebrafish were generated and vascular development monitored. Finally, miR-125a-/- ECs and zebrafish embryos were treated with an inhibitor of PFKFB3, 3PO. Results: Synovial expression of miR-125 was significantly decreased in PsA versus OA synovial tissue, levels of which were associated with macroscopic and microscopic synovial vascularity. Decreased expression of miR-125a in HMVEC resulted in increased tube formation, invasion and migration properties. Inhibition of miR-125 promoted a metabolic shift towards glycolysis with parallel changes at the gene level. Ex vivo, increased vascular expression of glycolytic markers was observed in PsA versus OA synovial tissue. In vivo, miR-125a knockout zebrafish displayed increased vascular sprouting similar to the irregular nature of the vasculature within the PsA synovium. Finally, 3PO significantly inhibited anti-miR-125a-induced mechanism whilst normalising the vascular development of miR-125a -/- embryos. Conclusions: Decreased expression of miR-125 in PsA synovium and in-vivo models was strongly associated pro-angiogenic mechanisms. Elevated glycolysis following miR-125 inhibition enabled ECs to meet the increased energy demands for new vessel formation. Correcting these miRNA deficiencies and their resulting metabolic shift, either by conventional pharmacological or as novel drug targets, may provide therapeutic benefit, especially in early disease. Disclosure of Interest: None declared.